1997
DOI: 10.1111/j.1600-051x.1997.tb01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Gingival phenotypes in young male adults

Abstract: In a previous study on 42 young adult, periodontally healthy subjects without any attrition, abrasion or crown restoration, gingival thickness (GTH) was determined at facial aspects of premolars, canines and incisors by a novel ultrasonic device. GTH strongly depended on periodontal probing depth, width of gingiva (WG), and tooth type. Whereas the ratio of crown width to its length (CW/CL) was not identified as an explanatory variable, a significant influence of the subject was ascertained. The aim of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
201
2
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(226 citation statements)
references
References 7 publications
12
201
2
11
Order By: Relevance
“…a cluster had a significantly thicker and wider gingiva, while another cluster showed normal gingival thickness but a narrow zone of keratinized tissue. 11 The present study demonstrated that the plaque and gingival indices showed a negative correlation with the width of keratinized tissue among the cases. This finding is in agreement with that of a study conducted by Lang and Loe, who demonstrated that areas of minimum width of attached gingiva may by their increased mobility facilitate subgingival plaque deposition.…”
Section: Discussionmentioning
confidence: 67%
“…a cluster had a significantly thicker and wider gingiva, while another cluster showed normal gingival thickness but a narrow zone of keratinized tissue. 11 The present study demonstrated that the plaque and gingival indices showed a negative correlation with the width of keratinized tissue among the cases. This finding is in agreement with that of a study conducted by Lang and Loe, who demonstrated that areas of minimum width of attached gingiva may by their increased mobility facilitate subgingival plaque deposition.…”
Section: Discussionmentioning
confidence: 67%
“…Recall studies indicate thickness of the gum (gingival biotype) is more decisive than the amount of keratinized gingiva to prevent future gum recession 24 . It is important to highlight that an important factor to increase the risk of future gingival recession is a thin gingival biotype 25,26 . It should be emphasized the purpose of a muco-gingival surgery should not only increase the width of keratinized tissue, but also its thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Gingival recession is the apical migration of the gin gival margin to the cementoenamel junction, either coagnated with inflammatory periodontal disease 1 and mechanical trauma 2 or with the presence of a host of predisposing factors that include tooth malposition and root prominence, gingival phenotype, 3 underlying alveolar dehiscence, 4,5 orthodontic tooth movement, 4,6 aberrant frenulum attachment 7 and iatrogenic restorative and periodontal treatmentrelated factors (surgical recession). 8 For the correction and management of muco gingival deformities and defects, variety of perio dontal plastic surgery procedures have been described in the literature, with the aim to set up and preserve the dentition and periodontium, healthy and functional with most favorable esthetics throughout the life time.…”
Section: Introductionmentioning
confidence: 99%